Personalized Online Education"”A Crowdsourcing Challenge - Weld, Daniel S.; Adar, Eytan; Chilton, Lydia; Hoffmann, Raphael; Horvitz, Eric; Koch, Mitchell; Landay, James; Lin, Christopher H.; Mausam (In Workshops at the Twenty-Sixth AAAI Conference on Artificial Intelligence, 2012)
Interest in online education is surging, as dramatized by the success of Khan Academy and recent Stanford online courses, but the technology for online education is in its infancy. Crowdsourcing mechanisms will likely be essential in order to reach the full potential of this medium. This paper sketches some of the challenges and directions we hope HCOMP researchers will address.